A new dropper-type gas flow measuring method based on weighing principle. (November 2017) - Zhang, Shiwei; Sun, Kun; Han, Feng; Zhao, Fan
Abstract: The dropper-type gas flow measuring apparatus is widely used in the vacuum pumping speed measurement. An innovative method based on the weighing principle was proposed in the paper. The structure and working principle of the dropper-type gas flow measuring apparatus is introduced. An electronic scale was placed under the storage tank to measure the oil mass into dropper. The corresponding formulas of gas flow are deduced and the error analysis of measuring accuracy is carried out. Comparing to the disadvantages of the original measuring method, the characteristics of new method was analyzed. A miniature measuring apparatus was set up in the laboratory, and the pumping speed curve of a K-200 diffusion pump was measured by experiment. The feasibility and convenience of the measuring apparatus were verified. This improvement can provide theoretical support and reference method for achieving automatic measurement of vacuum pumping speed and minimal gas flow. Highlights: New gas flow measuring apparatus and method are put forward in the paper. The Characteristics of new method is analyzed. A miniature measuring apparatus is set up according to the method. The feasibility and convenience of the measuring apparatus are verified.